1994
DOI: 10.1021/ma00089a002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Poly(aminocarbophosphazenes)

Abstract: The cyclic carbophosphazene N3P2CCI5 undergoes thermal ring-opening polymerization at 120 °C to yield poly(pentachlorocarbophosphazene), [NgPgCCleln, as a hydrolytically sensitive elastomer. Treatment of this polymer in solution with primary and secondary alkylamines yielded poly(aminocarbophosphazenes) [NgPüCtNRiRü)^,, where Ri = H, R2 = nPr or 'Pr, and Ri = Ri = Me or Et. These polymers are also sensitive to moisture. An anilino/dimethylamino mixed-substituent polymer, [NgPiCtNHPh),-(NMeü)y(Cl)z]n (x = 1.50,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…Small amounts of residual chlorine probably arise from the formation of polymeric ammonium salts of the type RR′NH 2 + Clwhere the basic poly[(amino)thionylphosphazene] competes with excess amine as an HCl acceptor. Similar behavior has been reported during the aminolysis of poly[(halogeno)carbophosphazenes] 26 as well as the classical polyphosphazene [Cl 2 PdN] n . 27 The 31 P NMR spectra showed resonances at a significantly lower field (ca.…”
Section: Synthesis and Structural Characterization Of The Poly[(amino...supporting
confidence: 80%
“…Small amounts of residual chlorine probably arise from the formation of polymeric ammonium salts of the type RR′NH 2 + Clwhere the basic poly[(amino)thionylphosphazene] competes with excess amine as an HCl acceptor. Similar behavior has been reported during the aminolysis of poly[(halogeno)carbophosphazenes] 26 as well as the classical polyphosphazene [Cl 2 PdN] n . 27 The 31 P NMR spectra showed resonances at a significantly lower field (ca.…”
Section: Synthesis and Structural Characterization Of The Poly[(amino...supporting
confidence: 80%
“…The aryloxy chains were further characterized by the same group in 1991, and it was found that the poly(carbophosphazene) skeleton is much less flexible than PP, probably due to the inherent differences in the π-bonding nature of CN and PN double bonds. Following these initial works, additional structures, like various aminocarbophosphazenes, have been synthesized . In addition, closely related copolymers, polythiophosphazenes 20 and polythionylphosphazene, both presenting the SNPNPN backbone sequence have been obtained by ROP.…”
Section: Introductionmentioning
confidence: 99%
“…Following these initial works, additional structures, like various aminocarbophosphazenes, have been synthesized. 19 In addition, closely related copolymers, polythiophosphazenes 20 and polythionylphosphazene, 21 both presenting the SNPNPN backbone sequence have been obtained by ROP. We refer the reader to ref 22 for a detailed review of these inorganic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal ROP of a cyclic carbophosphazene was used to prepare the chlorinated polymeric species (23), which undergoes halogen replacement reactions with nucleophiles such as aryloxides and aniline to yield hydrolytically stable poly(aryloxycarbophosphazenes) (24) (M w = ca 10 5 , M n = 10 4 ) (eq. 23) (88)(89)(90)(91). The polymer backbone in these materials was found to be less flexible than in classical polyphosphazenes.…”
Section: Polycarbophosphazenesmentioning
confidence: 98%
“…The reaction of (23) with alkylamines has also been studied (91). The resulting poly(alkylaminocarbophosphazenes) are sensitive to hydrolysis.…”
Section: Polycarbophosphazenesmentioning
confidence: 99%